Phylogenetic and codon usage analysis of atypical porcine pestivirus (APPV) - Shuonan Pan (Taylor & Francis Group, 2020)
Atypical porcine pestivirus (APPV) has been identified as the main causative agent for congenital tremor (CT) type A-II in piglets, which is threatening the health of the global swine herd. However, the evolution of APPV remains largely unknown. In this study, phylogenetic analysis showed that APPV could be divided into three phylogroups (I, II, and III). Phylogroups I and II included viral strains from China, while phylogroup III contained strains from Europe, North America, and Asia. Phylogroups I and II are tentatively thought to be of Chinese origin. Next, compositional property analysis revealed that a high frequency of nucleotide A and A-end codons was used in the APPV genome. Intriguingly, the analysis of preferred codons revealed that the AGA[Arg] and AGG[Arg] were overrepresented. Dinucleotide CC was found to be overrepresented, and dinucleotide CG was underrepresented. Furthermore, it was found that the weak codon usage bias of APPV was mainly dominated by selection pressures versus mutational forces. The codon adaptation index (CAI), relative codon deoptimization index (RCDI), and similarity index (SiD) analyses showed that the codon usage patterns of phylogroup II and III were more similar to the one of a pig than phylogroup I, suggesting that phylogroup II and III may be more adaptive to pigs. Overall, this study provides insights into APPV evolution through phylogeny and codon usage pattern analysis.